Transfer of mechanical energy during the shot put - Blazkiewicz, M.; Lyson, B.; Chmielewski, A.; Wit, A. (Journal of Human Kinetics, 2016)
The aim of this study was to analyse transfer of mechanical energy between body segments during the glide shot put. A group of eight elite throwers from the Polish National Team was analysed in the study. Motion analysis of each throw was recorded using an optoelectronic Vicon system composed of nine infrared camcorders and Kistler force plates. The power and energy were computed for the phase of final acceleration of the glide shot put. The data were normalized with respect to time using the algorithm of the fifth order spline and their values were interpolated with respect to the percentage of total time, assuming that the time of the final weight acceleration movement was different for each putter. Statistically significant transfer was found in the study group between the following segments: Right Knee - Right Hip (p = 0.0035), Left Hip - Torso (p = 0.0201), Torso - Right Shoulder (p = 0.0122) and Right Elbow - Right Wrist (p = 0.0001). Furthermore, the results of cluster analysis showed that the kinetic chain used during the final shot acceleration movement had two different models. Differences between the groups were revealed mainly in the energy generated by the hips and trunk.